Antimicrobial activity and phytochemicals compound profile of ethanol extract Moringa leaf (Moringa oleifera) compounds by FTIR - Ningsih, Arista Wahyu; Safıra, Aulia Dinda; Giovano, Andre; S.Klau, Ivan Charles (Faculty of Pharmacy, Universitas Pancasila, 2024)
Moringa plants are known in various parts of the world as a type of vegetable plant that is rich in nutrients and has multiple properties, one of which is as an antimicrobial. This research was conducted to test the antimicrobial inhibition of Moringa leaf decoction and ethanol extract against the growth of Escherichia coli and Aspergillus niger. The antimicrobial test in this study used the Disc diffusion method using various concentrations, including 25%, 50%, 75%, and 100%. There were two test samples, Moringa leaf decoction and ethanol extract using the maceration method with 96% ethanol solvent. In addition to the test group, there was also a control group, namely a positive control using chloramphenicol and ketoconazole antibiotics, negative control using aquadest as a decoction solvent, and DMSO as an extraction solvent. The ethanol extract was identified by the FTIR method. The results showed that Moringa leaf decoction and Moringa leaf ethanol extract could be used as antibacterial. Inhibition zones on Escherichia coli bacteria produced at concentrations of 25%, 50%, and 75% had a weak zone of inhibition category for both decoction and ethanol extract of Moringa leaves. Meanwhile, at a concentration of 100%, the decoction has a weak zone of inhibition and 100% ethanol extract of Moringa leaves can inhibit 8.25 mm which is included in the medium category. The inhibition zones of the fungus Aspergillus niger produced at concentrations of 25%, 50%, 75%, and 100% had no inhibition on both the decoction and ethanol extract of Moringa leaves. From the analysis of functional groups using the FTIR method, it can be predicted that in the Moringa leaf extract with methanol as solvent there are groups of phenolic compounds or flavonoids.